Pengaruh Komunikasi terhadap Kinerja Pegawai pada Satuan Polisi Pamong Praja dan Kebakaran Kabupaten Seram Bagian Barat - Demiwa, Wa; Simarmata, Ricardo Manarintar (Jurnal Marketing, 2024)
The purpose of this study was to determine and analyze the effect of communication on employee performance at the Civil Service Police and Fire Unit of West Seram Regency. The analysis methods used in this study are quantitative analysis and simple linear regression analysis. Quantitative Analysis shows that communication at the Civil Service Police and Fire Unit of West Seram Regency has an average value of 3.75 which is interpreted as good, while employee performance has an average value of 3.21 which is interpreted as quite good. The results of the regression analysis show that communication has a positive effect on employee performance at the Civil Service Police and Fire Unit of West Seram Regency. Based on these results, it can be concluded that the better the communication, the better the employee performance. To improve it, employees must always communicate something related to work to colleagues and leaders so that the work that is done can be done well and make work performance better. Keywords: Communication, Employee Performance.